Determinants of Differential Rent Changes: Mean Reversion versus the Usual Suspects. (28th January 2016) - Verbrugge, Randal; Dorfman, Alan; Johnson, William; Marsh, Fred; Poole, Robert; Shoemaker, Owen
Abstract : This is a hedonic regression study of the 2001–2004 and 2004–2007 rent growth of 18, 000 rental units. Which variables matter: Location? Age? Rent level? Occupancy duration? Structure type? The answers deepen understanding of the rental market and help guide statistical agency practice. We document significant rent stickiness. Initial relative rent level is the best predictor, mainly because of mean reversion. (This problem likely extends well beyond the present study.) "Location" comes in second, though often not statistically significant: the relative value of location is persistent. Age and occupancy duration are also notable. Our findings support statistical agency practices.